50 x 2 = 30 000 = the SPORE equation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
lt is now 100 months since the first edition of SPORE was published. Fifty editions in two languages have rolled from the printing presses and the subscription list has reached 30,000. This is the SPORE equation! But the coincidence of numbers has...